Ketinggian Pangkas Berat dan Pupuk Organik terhadap Biomassa dan Flavonoid Daun Kemuning pada Panen Pertama dan Kedua - Eman Ayu Sasmita Jati, Gusti; Arifin Aziz, Sandra; Melati, Maya (Jurnal Hortikultura Indonesia, 2019)
Harvesting of orange jessamine (Murraya paniculata (L.) Jack.) by pruning at the same height continously causes the decreasing of production. It is lack of previous report on the heavy pruning application in orange jessamine. The study aimed to determine the appropriate height of heavy pruning and level of fertilizers application in order to maintain stable yield production of orange jessamine leaves. The study was conducted from July 2015 to July 2016 at the Organic Experimental Station of Bogor Agricultural University in Cikarawang Bogor. The experiment used a randomized block design with two factors and four replications. The first factor was pruning height consisted of 45, 60 and 75 cm above the soil surface. Height of 75 cm was designed as control. The second factor was combination of chicken manure (CM) and rice-husk ash (RA), i.e., without fertilizer (control), 7 kg CM + 3 kg RA, and 14 kg CM + 6 kg RA per plant. The harvest was done two times with four month intervals. The results showed that the pruning height of 60 cm above the soil surface was the best heavy pruning for growth, production and the total content of flavonoids of orange jessamine plants aged 45-57 month after planting after 4-6 harvests, while fertilization treatments did not produce significantly different results. Keywords: chicken manure, pigment content, pruning height, rice-husk ash